Argumentasi Kasasi Putusan Bebas Judex Facti Akibat Kesalahan Penerapan Hukum Perkara Memakai Surat Palsu Atau yang Dipalsukan - Baktiakbar, Adzamayah Satmuharrulys (Verstek, 2019)
This research aims to fnd out the conformity argumentation cassation from Public Prosecutor against the acquittal due to misapplied the law in cases of use false document or falsifed document have been in accordance with Article 253 Criminal Procedure Code. This writing is a normative law research orcommonly called the doctrinal legal research. The results of the discussion to explain that the reasons for the appeal fled Public Prosecutor against the decision of Judex Facti Cirebon District Court has been in accordance with the provisions of Article 253 Criminal Procedure Code about the reason for the cassation request. The reasons for the appeal fled Public Prosecutor has been in accordance with the provisions of Article 253 paragraph (1) letter a and Article 253 paragraph (1) letter b Criminal Procedure Code. The Cirebon District Court that has investigated and adjudicated the case on behalf of the defendant R. HARDADI has made a mistake by not applying the rule of law namely misinterpreted the meaning of falsedocument or falsifed document in the primary charge, not applied the law of evidence, and misinterpreted the meaning of “Deliberately use false document or falsifed document as if it were true” in the subsidiary charge, and the method of adjudicated were not implemented the provisions of Article 197 paragraph (1) letter d namely the Cirebon District Court was ignore witnesses testimony, Article 185 paragraph (6) letter a namely the Cirebon District Court was not paying attention to the suitability of witnesses testimony andevidence, and Article 187 letter c of the Criminal Procedure Code namely the Cirebon District Court was neglect to assess evidence . The reason cassation Public Prosecutor has met the provisions of Article 253 paragraph (1) letter a and Article 253 paragraph (1) letter b Criminal Procedure Code namely the rule of law is not applied or not applied as it should be and the method of adjudicated were not implemented under the provisions of the law